ANALISIS PENGARUH ETIKA PERSONAL SELLING TERHADAP KEPUASAN NASABAH ASURANSI JIWA PT. SUNLIFE FINANCIAL CABANG MEDAN - Deri Arifin Nur Marpaung; Nur Ahmadi Bi Rahmani; Laylan Syafina (CV. Denasya Smart Publisher, 2024)
This research is an analysis of the influence of personal selling ethics on life insurance customer satisfaction. The object of this research is PT. Sunlife Financial Medan Branch. The problem of this research is whether Order Takers, Order Getters, Order Creators, and whether Order Takers, Order Getters, Order Creators have an effect on PT life insurance customer satisfaction. SunLife Financial Medan Branch. The purpose of this research is to find out whether Order Takers, Order Getters, Order Creators, and whether Order Takers, Order Getters, Order Creators have an effect on PT life insurance customer satisfaction. SunLife Financial Medan Branch. The research method used is a comparative quantitative method. The comparative quantitative method has been chosen to obtain the data needed in this study. This research used 93 respondents and all respondents were customers of PT. Sunlife Financial Medan Branch. Data analysis used the SPSS 16.0 computer program. The results of this research. The test results show that it is known that the coefficient of determination is 50.8%, which means that customer satisfaction can be explained by the variables order takers, order gettors and order creators. And this means that 49.2% is influenced by other variables that are not within the scope of this research. Thus, the hypothesis which states that order takers, order getters and order creators have a significant effect on customer satisfaction can be accepted.